Fascial plane mapping for superficial tumor resection in dogs. Part II: Forelimb. Issue 1 (22nd July 2021) - Latifi, Max; Skinner, Owen T.; Schroeder, Mikayla M.; Mickelson, Megan A.
Abstract: Objective: To detail the qualitative fascial categories and fascial intersections of the forelimb of the dog to facilitate preoperative planning for superficial cancers. Study Design: Qualitative anatomical study. Sample Population: Three male and four female mixed breed canine cadavers weighing approximately 20–35 kg. Methods: The skin and subcutaneous fat were excised. Fascial planes were incised and elevated to allow exploration of their quality and borders. Fascia was categorized as type I (discrete sheets), type II (tightly adhered to thin muscles), type III (tightly adhered to thick muscles), or type IV (associated with periosteum). Photographs of specimens were digitally modified with overlays to map tissue types. Results: Differences between the cadavers used were largely based on muscle mass and sex, with minimal other subjective differences affecting fascial mapping. The fasciae of the forelimb were largely type II or type III, with type I fascia at the antebrachium and type IV fascia at the olecranon, scapular spine, and accessory carpal bone. Fascial integrity was often questionable or lacking distal to the distal quarter of the antebrachium. Conclusion: The fascial types and integrity of the forelimb varied with anatomic location with thin or absent fascia for surgical use at the elbow, carpus, and manus. Clinical Significance: This study provides information for preoperative planning and excision of superficial tumors of the forelimb. Knowledge of the potential limitations of fascia to provide a deep margin may influence selection of treatment modalities.